2011
DOI: 10.2298/abs1103685t
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of extracts from twelve Centaurea species from Turkey

Abstract: Members of the genus Centaurea (Asteraceae) have been used in traditional plant-based medicine. The methanol extracts of twelve Centaurea species, of which five are endemic to Turkey flora, were screened for antibacterial activity against four bacteria (Escherichia coli, Bacillus cereus, Salmonella enteritidis, Staphylococcus aureus). The antibacterial activity was evaluated by the microdilution method and the minimum inhibition concentrations (MIC) of the extracts were determined. C. cariensis subsp. mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 23 publications
4
30
0
1
Order By: Relevance
“…Several studies are present in literature reporting the use of liquid chromatography electrospray ionization tandem mass spectrometry to perform quantitative analyses [18,19]. In this study, an accurate method on a mass spectrometer equipped with a The antibacterial effect of C. balsamita seen in this study has been reported previously in eight Centaurea species [4,9]. Sımilarly, the antifungal activity of C. balsamita has been reported in Candida krusei [10].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Several studies are present in literature reporting the use of liquid chromatography electrospray ionization tandem mass spectrometry to perform quantitative analyses [18,19]. In this study, an accurate method on a mass spectrometer equipped with a The antibacterial effect of C. balsamita seen in this study has been reported previously in eight Centaurea species [4,9]. Sımilarly, the antifungal activity of C. balsamita has been reported in Candida krusei [10].…”
Section: Discussionsupporting
confidence: 52%
“…In Turkish traditional medicine, these species are widely used as expectorant, antidiabetic, antipyretic and antidiarrhoeal [2]. Centaurea species are known to have various biological activities such as antimicrobial [4], antifungal [5], antiinflammatory [6], antiulcerogenic [7], antioxidant [8], antiplasmoidal [9], antiprotozoal [4], cytotoxic [9,10] and anticancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…; Tekeli et al . ), AChE inhibitory (Aktumsek et al . ), antiulcerogenic and immunologic activities (Arif et al .…”
Section: Introductionmentioning
confidence: 99%
“…Flowers of P. granatum, M. chamomilla and S. officinalis, leaves of M. piperita and R. officinalis and U. dioica roots were fully separated and milled. In this stud, Soxhlet apparatus was used for extraction and according to Tekli et al method also Rotary evaporation apparatus was used to evaporate methanol (48). Then 15 g of each powder was dissolved in 300 mL methanol 96% (Merck, Germany) and shaked for 24 hours by shaker (KS 130 Control Mixing Orbital Shaker, IKA Company, Germany) after necessary time shaking, these solvents were filtered by Whatman NO.…”
Section: The Plant Extraction Methodsmentioning
confidence: 99%